Biointensive Management of Okra Fruit Borers using Braconid Parasitoids (Braconidae: Hymenoptera) - G Thanavendan; S Jeyarani (Tropical Agricultural Research, 2010)
Okra (Abelmoschus esculentus (L.) Moench) is ravaged by many insect pests from germination to harvest. Sucking pests in the early stage and the fruit borers, Earias vittella Fabricius and Helicoverpa armigera (Hübner) in the later stage causes extensive damage to fruits causing 69 per cent yield loss. In recent years, increased interest has been shown towards biological control following unsatisfactory results with the application of conventional insecticides. Horticultural crops, chiefly fruit crops, provide a stable environment offering good opportunity for biological control. Hence, investigations were carried out during 2007-2008 to assess the potential of braconid parasitoids against okra fruit borers. The results revealed that the combination of Trichogramma chilonis + Chelonus blackburni + Bracon brevicornis and C. blackburni + B. brevicornis were more effective to lower larval population of E. vittella and H. armigera which was next to Endosulfan 35 EC after three releases/spray. Similar trend was also observed for per cent fruit damage on both number and weight basis. Combination of T. chilonis + C. blackburni + B. brevicornis and C. blackburni + B. brevicornis recorded higher yield which was on par with endosulfan 35 EC. The results of the trials widened the scope of utilizing the braconid parasitoids in the biosuppression of fruit borers on okra. DOI: http://dx.doi.org/10.4038/tar.v21i1.2585 Tropical Agricultural Research Vol. 21(1): 39-50 (2009)